2020
DOI: 10.4103/njms.njms_35_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polycaprolactone scaffold for guided bone regeneration in maxillary and mandibular defects: A clinical study

Abstract: Objective: This study was carried out to assess bone regeneration following the use of polycaprolactone (PCL) scaffold in maxillary and mandibular osseous defects. Materials and Methods: This prospective study included ten patients with maxillary or mandibular osseous defects present due to enucleation of periapical cysts or alveolar clefts requiring bone grafting and for lateral ridge augmentation that were treated with PCL scaffold. The patients were assessed clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…Scaffold biomaterials for successful tooth regeneration applications should have some requirements such as being biocompatible, biodegradable, and possess mechanical properties that are consistent with the implanted area as well as being used in the appropriate amount and with an accessible volume of porosities for the diffusion of oxygen, cells, and nutrients [ 6 , 7 ]. To date, many polymeric materials have been reported to create biodegradable scaffolds for dental tissue engineering including poly(lactide) (PLA) [ 8 ], poly(lactide-co-glycolide) (PLGA) [ 9 , 10 ], and polycaprolactone (PCL) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold biomaterials for successful tooth regeneration applications should have some requirements such as being biocompatible, biodegradable, and possess mechanical properties that are consistent with the implanted area as well as being used in the appropriate amount and with an accessible volume of porosities for the diffusion of oxygen, cells, and nutrients [ 6 , 7 ]. To date, many polymeric materials have been reported to create biodegradable scaffolds for dental tissue engineering including poly(lactide) (PLA) [ 8 ], poly(lactide-co-glycolide) (PLGA) [ 9 , 10 ], and polycaprolactone (PCL) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive response to the implants, with no pain, swelling or severe inflammation, bone formation within the scaffolds was minimal after 9 months. [ 89 ] This result could be attributed to the inert nature of the scaffold material. It is important to notice that this case study, as mentioned above, reported the clinical treatment of a small defect.…”
Section: Vascularization Strategies For Mandibular Regenerationmentioning
confidence: 99%
“…For example, during tooth extraction, 3D PCL scaffolds inserted into the tooth socket have allowed for improved alveolar ridge preservation and bone healing during clinical trials . Further, PCL scaffolds have been utilized for treatment of facial fracture to promote bone healing. In one study, 3D-printed, patient-specific PCL scaffolds were fabricated for complex maxillary defects, , thus highlighting the advanced biofabrication that can leveraged with PCL. Cosmetically, PCL-based material has been utilized as a soft tissue filler in various applications such as correction of nasolabial folds, dorsal hand volume loss due to aging and facial lifting. , 3D PCL scaffolds have further been used in clinical rhinoplasty procedures, with 98.0% of patients showing no postoperative infection-related foreign body reaction or distinct abnormal reaction .…”
Section: Current Progress Of Pcl In Cardiac Tissue Engineeringmentioning
confidence: 99%
“…159 Further, PCL scaffolds have been utilized for treatment of facial fracture to promote bone healing. 160−163 In one study, 3D-printed, patient-specific PCL scaffolds were fabricated for complex maxillary defects, 160,161 thus highlighting the advanced biofabrication that can leveraged with PCL. Cosmetically, PCL-based material has been utilized as a soft tissue filler in various applications such as correction of nasolabial folds, 164 dorsal hand volume loss due to aging 165 and facial lifting.…”
Section: Influence Pcl Propertiesmentioning
confidence: 99%